2015
DOI: 10.1371/journal.pone.0140850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grammaticality and Morphological Complexity on the P600 Event-Related Potential Component

Abstract: We investigated interactions between morphological complexity and grammaticality on electrophysiological markers of grammatical processing during reading. Our goal was to determine whether morphological complexity and stimulus grammaticality have independent or additive effects on the P600 event-related potential component. Participants read sentences that were either well-formed or grammatically ill-formed, in which the critical word was either morphologically simple or complex. Results revealed no effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…Furthermore, we chose one time window for the rule-generalization test (250-400 ms) to assess early positivity, and one for the control task (350-500 ms) to assess the N400 effect. These time-windows are within the expected time ranges of the N200 (Folstein & Van Petten, 2008;Nieuwenhuis, Yeung, & Cohen, 2004), the N400 (Frenzel et al, 2010;Morris & Holcomb, 2005;Proverbio & Riva, 2009; see Kutas & Federmeier, 2011 for review), and the P600 (Dowens et al, 2011;Frenzel et al, 2010;Mehravari, Tanner, Wampler, Valentine, & Osterhout, 2015;Morris & Holcomb, 2005) component, respectively. We used repeated measures analyses of variance to assess the effects of experimental conditions and electrode locations.…”
Section: Eeg Recording and Data Processingsupporting
confidence: 62%
“…Furthermore, we chose one time window for the rule-generalization test (250-400 ms) to assess early positivity, and one for the control task (350-500 ms) to assess the N400 effect. These time-windows are within the expected time ranges of the N200 (Folstein & Van Petten, 2008;Nieuwenhuis, Yeung, & Cohen, 2004), the N400 (Frenzel et al, 2010;Morris & Holcomb, 2005;Proverbio & Riva, 2009; see Kutas & Federmeier, 2011 for review), and the P600 (Dowens et al, 2011;Frenzel et al, 2010;Mehravari, Tanner, Wampler, Valentine, & Osterhout, 2015;Morris & Holcomb, 2005) component, respectively. We used repeated measures analyses of variance to assess the effects of experimental conditions and electrode locations.…”
Section: Eeg Recording and Data Processingsupporting
confidence: 62%
“…A number of studies have reported that syntactically and morphosyntactically anomalous words elicit a P600 effect (e.g., Friederici, Hahne, & Mecklinger, ; Hagoort, Brown, & Groothusen, ; Hagoort, Wassenaar, & Brown, ; Mehravari, Tanner, Wampler, Valentine, & Osterhout, ; Osterhout & Holcomb, ; Osterhout & Mobley, ; Tanner & Bulkes, ), as do some words in well‐formed but complex sentences (e.g., garden path sentences: Gouvea, Phillips, Kazanina, & Poeppel, ; Kaan & Swaab, ; Osterhout, Holcomb, & Swinney, ). This set of syntax‐related findings led some to argue that the P600 reflects essentially syntactic processes (e.g., Allen, Badecker, & Osterhout, ; Gouvea et al, ; Kos, Vosse, van den Brink, & Hagoort, ; Osterhout, Mckinnon, Bersick, & Corey, ; Osterhout & Nicol, ).…”
mentioning
confidence: 99%
“…That is, recent studies note that there are no clear processing difficulties in grammatical sentences with singular heads and plural attractors (e.g., “The winner of the trophies was … ”) compared to singular‐singular head‐attractor configurations. This finding has led some to postulate that establishment of subject‐verb agreement dependencies utilizes a combination of prediction and retrieval mechanisms (Dillon, Mishler, Sloggett, & Phillips, ; Lago, Shalom, Sigman, Lau, & Phillips, ; Parker & Phillips, ; Tanner, Nicol, & Brehm, ; Wagers et al, ; see also Mehravari et al, ; Tanner & Bulkes, ). On this account, morphosyntactic agreement features for the verb are predicted upon encountering the head NP.…”
mentioning
confidence: 99%
“…
Figure 4 Strontium isotope variation across southeastern Arabia and the Indo-Pakistani region, including the botanical remains found at Mleiha. Data 32 , 33 , 60 65 . Dark and light orange bands represent the range of archaeological cotton seeds and textiles from Mleiha, respectively.
…”
Section: Discussionmentioning
confidence: 99%